GAMBARAN SELF-MANAGEMENT MAHASISWA BK FKIP UNDANA DALAM MENGIKUTI PEMBELAJARAN PRAKTIKUM SELAMA MASA PANDEMI COVID-19 - Lolang Maria Masi; Imanuel Lohmay; Febriana . (Nusa Cendana University, 2021)
The COVID-19 pandemic is an external factor that affects the current learning process. Physical restrictions and social activities on a large scale do not allow learning to be conducted face-to-face, so that it has a major impact on learning activities that must be carried out practically. Self-management is an important adjustment aspect in participating in practical learning during the COVID-19 pandemic. This study aims to describe the self-management of FKIP UNDANA BK students in participating in practical learning during the Covid-19 pandemic. The sample in this study amounted to 58 students of the Guidance and Counseling study program at the University of Nusa Cendana. The sample selection technique used simple random sampling. This study uses a mixed method, namely quantitative and qualitative. Quantitative data collection is carried out through the distribution of an online questionnaire that is easily accessible (google form). While the qualitative method through FGD (Focus group Discussion) using the Zoom application with 10 semester V BK students. The results of data analysis showed that the self-management of BK students in participating in practical learning during the covid-19 pandemic was in the high category, namely 77.59%. It is hoped that student self-management in participating in practicum learning during the covid-19 pandemic is better in order to improve learning achievement, especially in practicum courses.